2023
DOI: 10.1002/ppul.26386
|View full text |Cite
|
Sign up to set email alerts
|

Dexamethasone versus methylprednisolone for critical asthma: A single center, open‐label, parallel‐group clinical trial

Abstract: Background: Evidence for the use of dexamethasone for pediatric critical asthma is limited. We sought to compare the clinical efficacy and safety of dexamethasone versus methylprednisolone among children hospitalized in the pediatric intensive care unit (PICU) for critical asthma. Methods: A prospective, single center, open-label, two-arm, parallel-group, nonrandomized trial among children ages 5−17 years hospitalized within the PICU from April 2019 to December 2021 for critical asthma consented to receive met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Much of the recent literature focuses on ongoing treatment of status asthmaticus in pediatric critical care units where it has been found that dexamethasone was not inferior to methylprednisone or hydrocortisone when comparing steroid's effect on length of time on continuous albuterol while hospitalized [27]. Dosing comparisons of methylprednisone 1 mg/kg/dose q6 h (max of 60 mg) versus dexamethasone 0.25 mg/kg/dose q6 h (max 15 mg) showed no difference in the hospital length of stay, duration of continuous albuterol or additional adjunctive medications [28 ▪▪ ].…”
Section: Asthmamentioning
confidence: 98%
“…Much of the recent literature focuses on ongoing treatment of status asthmaticus in pediatric critical care units where it has been found that dexamethasone was not inferior to methylprednisone or hydrocortisone when comparing steroid's effect on length of time on continuous albuterol while hospitalized [27]. Dosing comparisons of methylprednisone 1 mg/kg/dose q6 h (max of 60 mg) versus dexamethasone 0.25 mg/kg/dose q6 h (max 15 mg) showed no difference in the hospital length of stay, duration of continuous albuterol or additional adjunctive medications [28 ▪▪ ].…”
Section: Asthmamentioning
confidence: 98%
“…Dexamethasone is a promising option for systemic steroids given its dosing frequency and half-life. Roddy et al performed a single center, parallel group prospective study comparing IV dexamethasone and IV methylprednisolone during acute asthma exacerbations in the pediatric intensive care unit (PICU) 20 . Children 5-17 years of age were eligible to participate.…”
Section: Interventions For Pediatric Asthma Exacerbationsmentioning
confidence: 99%